Analisis Kesesuaian Perairan untuk Keramba Jaring Apung di Kecamatan Sirah Pulau Padang Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Rangga Bayu Kusuma Haris; Indah Anggraini Yusanti (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Haris et al, 2019. The Analysis of Water Suitability for Floating Net Sprouts in Sirah Pulau Padang, Ogan Komering Ilir District, South Sumatra Province. JLSO 8(1):20-30.The purpose of this study is to analyze the level of water suitability of the floating net sprouts in sirah pulau padang, ogan komering river, Serdang Menang Village, OKI South Sumatra Regency based on water physical and chemical parameters. This study was conducted on July - August 2018 at the Komering River, Ulak Jermun village, Terusan Menang Village, and Mangun Jaya Village, OKI District, South Sumatra. The data of sampling was divided into 3 stations, they were; station 1 was Ulak Jermun Village (3 ° 18'45.48